2020
DOI: 10.1163/18759866-bja10002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of past and present gobies: distinguishing Gobius and Pomatoschistus (Teleostei: Gobioidei) species using characters of otoliths, meristics and body morphometry

Abstract: Gobies (Gobiidae + Oxudercidae) are among the largest groups of extant marine fishes. Fossils of gobies are abundant since the Miocene, and many species have been reported so far. However, delimitation of fossil goby species is challenging because molecular markers and diagnostic traits such as the disposition of sensory head papillae are lost. This study provides, for the first time, an actualistic framework for the identification of fossil goby species. We focus on characters that can in principle be recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The main differences were related to overall sagittal shape, development, area of sagitta, the positions of the posterodorsal and anteroventral processes, the type of dorsal and ventral rims and the extent of convexity in the posterior part of ventral and dorsal margins. These characters were also recognized as distinctive in the evaluation of variability among phylogenetic lineages in Mediterranean Sea gobies (Lombarte et al ., 2006) and for species identification within the genus Gobius (Gut et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The main differences were related to overall sagittal shape, development, area of sagitta, the positions of the posterodorsal and anteroventral processes, the type of dorsal and ventral rims and the extent of convexity in the posterior part of ventral and dorsal margins. These characters were also recognized as distinctive in the evaluation of variability among phylogenetic lineages in Mediterranean Sea gobies (Lombarte et al ., 2006) and for species identification within the genus Gobius (Gut et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a rule, the sagitta of teleost species provides information at both generic and species level (Nolf 1985(Nolf , 2013. In the Gobioidei, the sagittae of congeneric species are generally similar in overall shape; they share the same sulcus morphology and often show similar degrees of convexity/concavity of the outer and inner faces (e.g., Nolf 2013;Gierl et al 2018;Gut et al 2020;Schwarzhans et al 2020a, b). However, the taxonomic interpretation of sulcus morphology, also in gobioid otoliths, is complicated by the fact that considerable variability can occur not only within a single species (unpublished data of BR, see also Fig.…”
Section: Relationships Between the New Genera And Remarks On Taxonomymentioning
confidence: 99%
“…Phylogenetic relationships of these extinct species with the extant Pomatoschistus and Knipowischia species are not yet established. Associating fossil sand goby otoliths with extant species is difficult because of potentially multiple homoplasies emerging from the shaping of the otolith morphology (Schwarzhans, 2014; Schwarzhans et al, 2017), even if the combination of qualitative (morphology) and quantitative (morphometry) approaches seem promising (Gierl et al, 2018; Gut et al, 2020). Moreover, several previously published studies (Huyse et al, 2004; Penzo et al, 1998; Thacker et al, 2019; Vanhove et al, 2012) demonstrated that these sand goby groups are not monophyletic and that some Pomatoschistus and Knipowitschia species belong to different genera (respectively, Ninnigobius and Orsinigobius ; Geiger et al, 2014; Thacker et al, 2019).…”
Section: Methodsmentioning
confidence: 99%